On the genus Iphinoe (Crustacea, Cumacea) from Japanese waters and the Sulu Sea, Philippines, with the description of two new species - Akiyama, Tadashi (Zootaxa, 2025)
Three species of the cumacean genus Iphinoe Bate, 1856, I. sagamiensis Gamô, 1958, I. indenticulata, Kim & Kim, 2020, and I. wakasaensis sp. nov. from Japan, Northwest Pacific are reported. Iphinoe sagamiensis is closely similar to I. wakasaensis, but lives in shallower water (4–101 m) than I. wakasaensis (96–200 m). Iphinoe indenticulata, originally described from the Yellow Sea, was collected from the muddy bottom of the Seto Inland Sea of Japan, at 15 m depth. The female specimens are described. Also described herein is Iphinoe suluensis sp. nov. from the Sulu Sea, Indo-West Pacific, which is similar to I. crassipes Hansen, 1895 and I. pokoui Le Loeuff & Intes, 1972, which are regarded as aberrant members of the genus. A key to the species of Iphinoe of Japan, Korea and China is provided.